Social Perception of Congregants Towards the Tafsir al-Ibri>z: (Living Qur'an Study at Majelis Ta'lim Masjid Sabilun Najah) - Nur Muhammad, Alfet Robi'; Nafillah, Fahma (Journal of Islamic and Social Studies, 2026)
This study explores the congregation’s response to the al-Ibriz Qur’anic exegesis sessions held at Majelis Ta’lim Sabilun Najah, which integrate scriptural interpretation with everyday life. The research aims to understand participants’ perceptions, their motivations for attending, and the implementation process of the study sessions. Employing a descriptive qualitative approach, data were collected through interviews with the instructor and participants, field observations, and supporting documentation. The findings reveal that the congregation responded positively, viewing the sessions as a means to enhance religious understanding, strengthen faith, and deepen spiritual awareness. Key motivational factors include the desire to broaden religious knowledge, pursue personal betterment, and attain life blessings. Thus, the al-Ibriz tafsir sessions play a vital role in reinforcing both spiritual and social values through a grounded, contextually relevant approach to religious learning.